2016
DOI: 10.1007/s11069-016-2532-5
|View full text |Cite
|
Sign up to set email alerts
|

The changing landscape of disaster volunteering: opportunities, responses and gaps in Australia

Abstract: There is a growing expectation that volunteers will have a greater role in disaster management in the future compared to the past. This is driven largely by a growing focus on building resilience to disasters. At the same time, the wider landscape of volunteering is fundamentally changing in the twenty-first century. This paper considers implications of this changing landscape for the resilience agenda in disaster management, with a focus on Australia. It first reviews major forces and trends impacting on disa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
100
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 108 publications
(103 citation statements)
references
References 40 publications
2
100
0
1
Order By: Relevance
“…McLennan et al () argue that the wider landscape of volunteering is changing in the twenty‐first century. They discern changes in the ways of organizing volunteering.…”
Section: Previous Research On Crisis Volunteerismmentioning
confidence: 99%
See 1 more Smart Citation
“…McLennan et al () argue that the wider landscape of volunteering is changing in the twenty‐first century. They discern changes in the ways of organizing volunteering.…”
Section: Previous Research On Crisis Volunteerismmentioning
confidence: 99%
“…This argument can be further strengthened by the fact that researchers increasingly often claim that the landscape of crisis volunteering undergoes significant change. For example, Hustinx and Lammertyn () (cited in McLennan, Whittaker, & Handmer, , p. 2032) conclude that we experience “a decline in ‘traditional’, long‐term, high‐commitment volunteering and a rise in more diverse, fluid, and episodic styles of volunteering.”…”
Section: Introductionmentioning
confidence: 99%
“…It seems almost paradoxical how researchers in this field continually discuss the need for more information and knowledge about emergent groups and their role in what McLennan et al. () have called the transforming “landscape of volunteering”. This side of the year 2000, there are signs of evolving conceptualization and marginal change.…”
Section: Concluding Discussionmentioning
confidence: 99%
“…They concluded that “…emergent citizens groups are likely to be even more prominent in the future than they are at present” (Stallings & Quarantelli, : 94). Much contemporary analysis seems to validate their prediction, bringing different forms of voluntary engagement and emergent groups to the forefront of both crisis research and disaster management policy (Barsky & Horan, ; Drabek, ; Heelsloot & Ruitenberg, ; Kendra & Wachtendorf, ; Lorenz, Schulze, & Voss, in press; McLennan, Whittaker, & Handmer, ; Rodriquez, Trainor, & Quarantelli, ; Scanlon, Helsloot, & Groenendaal, ; Wachtendorf, ). Whether or not this shift in empirical focus has also contributed to a conceptual common ground and better understanding in disaster research, however, remains an open question.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation